Design and Testing of Scientific-based SPLDV Flip Worksheets - Siswanto, Deny Hadi; Maretha, Dinda Genius Anggun; Alghiffari, Eka Kevin; Mahmudah, Kunti Robiatul (Indonesian Journal of Educational Science and Technology, 2024)
This research is motivated by the need for teaching materials that are suitable for use in the 21st century, such as utilizing technology in using teaching materials for classroom learning. The use of teaching materials such as worksheets at SMP Muhammadiyah 9 Yogyakarta has implemented a scientific approach but has not been combined with the use of technology. The use of technology in learning is very diverse and can be realized in various supporting applications, one of which is flipbooks. Therefore, it is necessary to use scientific worksheets using the flipbook application. This research designs scientifically based flip worksheets for the subject Systems of Linear Equations in Two Variables that are valid and practical at SMP Muhammadiyah 9 Yogyakarta. Research and Development Methods using the ADDIE model will help achieve the objectives of this research accurately. With the support of instruments such as subject matter experts, media experts, and input from class VIII students, the development of flip worksheets produced very valid results in terms of content and media, with percentages of 94.23% and 90.00% respectively. Meanwhile, for the practical aspect, students gave a percentage of 72.60%, categorizing flip worksheets that were designed as practical.